Psikodrama untuk Meningkatkan Empati Siswa di Sekolah Inklusif - Cahyani, Niki (INKLUSI, 2019)
In an inclusive education setting, students with disabilities often become victims of bullying due to a lack of regular students’ empathy. The purpose of this study was to determine the effectiveness of psychodrama in increasing the empathy of regular students towards students with disabilities in inclusive schools. The study was conducted using an experimental method with one group model pre and post-test design. Sampling was done by purposive sampling technique, with the number of subjects 15 regular students in SMP Muhammadiyah 2 Malang. Data collection was done by interview and empathy scale survey. The data obtained were then analyzed using paired sample t-tests (p = 0.000, N = 15, t = -9.439). The research concludes that psychodrama can increase the empathy of regular students towards disabled students in inclusive schools of Muhammadiyah 2 Malang Junior High School. [Dalam pelaksanaan pendidikan inklusif, siswa difabel sering menjadi korban perundungan (bullying) karena kurangnya empati siswa reguler. Tujuan penelitian ini adalah untuk mengetahui efektivitas psikodrama dalam meningkatkan empati siswa reguler terhadap siswa difabel di sekolah inklusif. Penelitian dilakukan dengan menggunakan metode eksperimen dengan model one group pre and post test design. Pengambilan sampel dilakukan dengan teknik purposive sampling, dengan jumlah subyek 15 siswa reguler di SMP Muhammadiyah 2 Malang. Pengumpulan data dilakukan dengan wawancara dan survei skala empati. Data yang diperoleh lalu dianalisis dengan menggunakan paired sample t test (p= 0.000, N= 15, t= -9.439). Penelitian ini menyimpulkan bahwa psikodrama dapat meningkatkan empati siswa reguler terhadap siswa difabel di sekolah inklusif SMP Muhammadiyah 2 Malang]